2019
DOI: 10.1186/s12894-018-0434-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prostate gland weight on the surgical and oncological outcomes of extraperitoneal robot-assisted radical prostatectomy

Abstract: BackgroundRobot-assisted radical prostatectomy (RARP) is performed by urologists as one of the surgical procedures for treating prostate cancer. Numerous studies have been published with regard to the impact of prostate weight on performing RARP but were limited by the insufficient number of patients and use of the transperitoneal approach. This study aimed to determine the effect of prostate gland weight on the surgical and short-term oncological outcomes of RARP using the extraperitoneal approach.MethodsIn t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 26 publications
3
24
2
Order By: Relevance
“…However, the benefit of the Wallace anastomosis remains unclear. Of note, single-center series reported higher rates of stricture with the Bricker method than with the Wallace techniques (25.3% vs 7.7%, respectively), 31 while a recent meta-analysis compared these two techniques and reported low and comparable risks of ureteroenteric stricture with the Bricker and the Wallace anastomosis (3% and 2%, respectively). 32 We prefer the Wallace I technique as it simplifies the ureteroileal anastomosis.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…However, the benefit of the Wallace anastomosis remains unclear. Of note, single-center series reported higher rates of stricture with the Bricker method than with the Wallace techniques (25.3% vs 7.7%, respectively), 31 while a recent meta-analysis compared these two techniques and reported low and comparable risks of ureteroenteric stricture with the Bricker and the Wallace anastomosis (3% and 2%, respectively). 32 We prefer the Wallace I technique as it simplifies the ureteroileal anastomosis.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…And then, we eliminated 153 studies based on screening the titles and abstract. After full‐text assessing of 45 studies were performed, eventually 22 studies (Allaparthi, Hoang, Dhanani, & Tuerk, ; Butow et al, ; Caliskan, Kaba, Koca, & Ozturk, ; Chang, Moon, Gianduzzo, & Eden, ; Chu et al, ; Descazeaud, Zerbib, Vieillefond, Debre, & Peyromaure, ; Foley, Bott, Thomas, Parkinson, & Kirby, ; Freedland et al, ; Galfano et al, ; Goetzl, Krebill, Griebling, & Thrasher, ; Hong et al, ; Kim et al, ; Labanaris et al, ; Lallas et al, ; Levinson et al, ; Marchetti, Shikanov, Razmaria, Zagaja, & Shalhav, ; Msezane et al, ; Olsson et al, ; Pettus et al, ; Yadav et al, ; Yasui et al, ; Zorn et al, ) were enrolled in our meta‐analysis. The characteristics of them were introduced in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al determined that higher blood loss was associated with larger prostate size in a series of 1168 RARPs. Nevertheless, the nal PSM rate did not signi cantly differ among divided-size subgroups23 . Tamhankar et al reviewed 1406 RARPs to…”
mentioning
confidence: 78%
“…PSM detected in radical prostatectomy (RP) specimens is considered a poor oncological outcome 6 ; however, its long-term effect on mortality remains uncertain 7 . Previous studies have reported several predictors for PSM, including prostate-speci c antigen (PSA) concentration, prostate weight 8 , obesity 9 , the histopathological ndings from biopsy and RP specimens 10 , surgeon experience 11 , pathologist interpretation 12 , surgical approach 13 , and surgical method [14][15][16][17] , may potentially in uence postoperative PSM. However, data from Asian countries regarding the prediction of PSM and BCR are still lacking owing to differences in PCa phenotypes between individuals in Asian and Western countries 18 .…”
Section: Introductionmentioning
confidence: 99%